DISCOVER trial - distal resection of the pancreas with or without coverage of the pancreatic remnant: study protocol of a randomised controlled trial - Hassenpflug, Matthias; Bruckner, Thomas; Knebel, Phillip; Diener, Markus K.; Büchler, Markus W.; Werner, Jens (Trials, 2013)
Distal pancreatectomy for benign and malignant tumours is the second most common surgical procedure on the pancreas. Postoperative pancreatic fistulas (POPF) represent the most significant clinical complication, causing prolongation of hospital stay and the need for additional diagnostic and therapeutic procedures. Although various techniques for preventing POPF have been evaluated, to date, there is no available technique that ensures closure of the pancreatic remnant.